Blending as a Word-Formation Process in Sundanese TikTok Content: A Qualitative Morphological Study (e-Journal of Linguistics, 2026)
This study investigated blending as a word-formation process in Sundanese TikTok content to examine how morphological creativity reflects local identity, humor, and digital sociolinguistic practices. A qualitative descriptive approach was employed, and data were collected from two Sundanese TikTok accounts and analyzed using Kemmer’s (2003) typology. 14 blended forms were identified, most of which were constructed through clipping and recombination of root words. The findings indicate that blending functions not only as a strategy for lexical economy but also as a medium for cultural expression, social commentary, and identity construction. In comparison with previous studies on English and Indonesian blending, the results demonstrate that Sundanese blends exhibit localized innovation within a global digital environment. It is concluded that blending represents a productive and expressive morphological strategy that contributes to the vitality of regional languages in online communication. Further research is recommended to examine blending practices across wider platforms and linguistic communities
Keywords: Sundanese language; word formation; blending,; morphology,; TikTok discourse